The experiences of adolescents living with a central venous access device: A qualitative analysis - Tania Chimuris-Bautista; Abbey Hyde; Claire Magner; Mary Hughes; Sri Paran (International Journal of Nursing Studies Advances, 2022)
Background: Central venous access devices are used in paediatric populations for specific chronic conditions requiring long-term treatment. Very little isknown about how young people experience living with such devices. Aim: To gain a deep understanding of adolescents’ (aged 12-17 years) experiences of living with a central venous access device from the perspective of the adolescents themselves, and of one of their parents. Design: A descriptive phenomenological design was chosen. Methods: The sample comprised 20 participants, 10 adolescents with a central venous access device who were purposefully selected from a paediatric unit in Ireland, along with one of each adolescent's parents. Five of the adolescents had a skin tunnelled catheter that partly sits outside the body; and five a totally implanted port contained within the body. Participants were interviewed in adolescent-parent dyads, and data were analysed using an established phenomenological method. Results: Findings are presented around three themes: (i) The process of receiving treatment; (ii) managing skin tunnelled catheters and totally implanted ports day-to-day; and (iii) activities of daily living with a skin tunnelled catheter or a totally implanted port. Participants tended to compare their current device with previously negative experiences of multiple needle punctures associated with peripheral cannula insertions. Participants were largely positive about the type of device the adolescent currently had. However, in terms of daily management of the device itself and engaging in daily activities, totally implanted ports were more favourable than skin tunnelled catheters. Participants with a totally implanted port tended to minimise the needle-stick experience to access to the totally implanted port's reservoir. Discussion: Findings from the present study on adolescents concur with those of previous studies on adults that found that individuals with a central venous access device were largely positively disposed to their device and tended to compare their experiences of it to previously negative experiences with peripheral cannula insertions. Findings also reflect existing research that has reported a favourable disposition to self-management of a central venous access device, and a greater freedom to engage in everyday activities for those with a totally implanted port compared to those with a skin tunnelled catheter. Conclusion: We conclude that the type of central venous access device may have a pervasive and important impact on the everyday lives of adolescents and this needs to be given appropriate weight in formal guidelines for clinicians.